Critical review: “Discipline survival guide for the secondary teacher” - St-Amand, Jerome (Special Education, 2017)
Critical review of Thompson, J. (2012). La gestion de classe au secondaire: Guide pratique [Discipline survival guide for the secondary teacher]. Montréal: éditions Chenelière.